2013
DOI: 10.1016/j.mayocp.2012.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Triggered Reticular Telangiectatic Erythema Induced by a Spinal Cord Stimulator

Abstract: In recent years, cutaneous complications have been reported after implantation of medical devices as a result of their widespread use. We report a case of reticular telangiectatic erythema (RTE) after replacement of a spinal cord stimulator. To date, the pathogenesis of RTE has been poorly understood. Some reports have suggested that heat is involved, whereas others seem to contradict this observation. In our thermographic study, we found that heat can cause RTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Investigators described a patient in whom a defective spinal cord stimulator induced localized hyperthermia and subsequent reticular telangiectatic erythema. Notably, the lesions began to dissipate several days after the device was switched off [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigators described a patient in whom a defective spinal cord stimulator induced localized hyperthermia and subsequent reticular telangiectatic erythema. Notably, the lesions began to dissipate several days after the device was switched off [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 This fact has led to some authors to hypothesize that its origin could be the heat and electric or magnetic fields generated by these devices. 1,3 However, it has also been reported following implantation of articular prosthesis. 1 Moreover, Morgan et al reported in 2005 three cases of a postsurgical sternal erythema with clinical and histopathological findings remarkably similar to our patient.…”
mentioning
confidence: 99%